Effectiveness of Quality Cognitional Therapeutic Group on Changing the Level of Meta-cognitive Beliefs in Cannabis Addicted Men - Saleheh Iranmanesh; Mahra Ranjbordar; Razieh Jalili; Mahdi Yousefvand; Banafsheh Hassanvand (Journal of Education and Community Health)
Aims: Today, addiction has become one of the most serious problems in human society that it leads to many deviance, anomalies, and crimes. The main purpose of this study was to determine the effectiveness of the quality cognitional therapeutic group in changing the level of meta-cognitive beliefs among the cannabis addicted men. Materials & Methods: This quasi-experimental study with pretest-posttest design with control group was carried out among 40 addicted men in Khorramabad city in 2018-2019. The subjects were selected using random sampling method and randomly assigned to experimental (n=20) and control (n=20) groups. The experimental group was trained in quality cognitional therapeutic group in 8 sessions. The Wales metacognitive beliefs questionnaire was used for data collection in pre-test and post-test phases. Data were analyzed by SPSS 21 software using univariate and multivariate analysis of covariance. Findings: By controlling the pretest effect, the quality of the cognitional therapeutic group in increasing the positive beliefs (F=39.48) and cognitive self-awareness (F=14.35), as well as on reducing cognitive dissonance (F=12.67), the uncontrollability, risk of thoughts (F=13.48) and need for thought control (F=12.20) had a significant effect (p=0.001). Conclusion: The quality cognitional therapeutic group is effective in increasing the level of positive metacognitive beliefs and decreasing the level of negative metacognitive beliefs in cannabis addicted men.